2022
DOI: 10.1111/jop.13380
|View full text |Cite
|
Sign up to set email alerts
|

Oral epithelium response of electronic cigarette users to electronic cigarette

Abstract: Background: Electronic cigarettes are increasing in popularity, but there is only little information on their biologic effects on the oral epithelium, the initial site exposed to electronic cigarette smoke. Methods:We assessed the oral epithelium response to electronic cigarettes by comparing the histology and RNA transcriptome (mRNA and miRNA) of healthy electronic cigarette vapers to nonsmokers. mRNA was assessed based on: (1) genome-wide;(2) genes previously identified as dysregulated in the oral epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…After the removal of duplicates, 822 unique abstracts were screened, resulting in the inclusion of 53 studies (Figure 1, Table 1). 12‐64 Out of the 53 included articles, 34 (64%) analyzed the effects of e‐cigarette use on human subjects or cell lines, 16 (30%) utilized an animal model to investigate the in vivo effects of e‐cigarette aerosol exposure, and 3 (6%) studied both human and animal models. Human studies included: (1) in vitro assessments of e‐cigarette aerosol, condensate, or e‐liquid exposure on primary cultured cells or immortalized cell lines derived from upper airway tissue, or (2) clinical studies using samples obtained from current or former e‐cigarette users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the removal of duplicates, 822 unique abstracts were screened, resulting in the inclusion of 53 studies (Figure 1, Table 1). 12‐64 Out of the 53 included articles, 34 (64%) analyzed the effects of e‐cigarette use on human subjects or cell lines, 16 (30%) utilized an animal model to investigate the in vivo effects of e‐cigarette aerosol exposure, and 3 (6%) studied both human and animal models. Human studies included: (1) in vitro assessments of e‐cigarette aerosol, condensate, or e‐liquid exposure on primary cultured cells or immortalized cell lines derived from upper airway tissue, or (2) clinical studies using samples obtained from current or former e‐cigarette users.…”
Section: Resultsmentioning
confidence: 99%
“…Reeve et al 29 There were no statistically significant histological or transcriptomic changes in the oral epithelium of e-cigarette users vs nonsmokers.…”
Section: Proinflammatory Procarcinogenicmentioning
confidence: 94%
“…Most studies rely on self-reports assessed with questionnaires (Table S1). In 11 studies (40)(41)(42)(43)(44)(45)(46)(47)(48)(49), cotinine or other nicotine metabolites have been determined in body uids (blood, saliva, urine), which allows the distinction between users of any tobacco/nicotine product (including NGPs) and NU as well as the extend of product use. However, it does not distinguish between NGP and CC use.…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…In 4 investigations (54)(55)(56)(57), NGP (mostly EC) use of at least 1 year was required for study participation. In another 5 studies (42,45,(58)(59)(60), mean NGP use durations between 2 and 3 year were reported. The longest average NGP use duration in the selected studies amounted to 6.4 (61), 9.2 (62), 12.2 (63) and 12.5 years (64).…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation